Establishment of a Simple and Efficient Single Spore Isolation Method for Gilled Mushroom (Research in Agriculture Livestock and Fisheries, 2025)
Single-spore isolation is a fundamental technique for exploring genetic diversity in fungi, particularly in heterothallic species like Pleurotus ostreatus. This study outlines a method for isolating single spores from fruiting bodies, aimed at facilitating genetic improvement of mushrooms. The approach is especially suitable for the laboratories of mushrooms which are not necessarily well-funded, requiring only basic laboratory equipment. It is simple, resistant to contamination, and highly efficient. Under sterile conditions, spores were collected from mature mushroom fruiting bodies using a sterilized cotton swab and subjected to serial dilutions in distilled water. Each dilution was plated on Potato Dextrose Agar (PDA) and then incubated, producing a consistent source of genetically uniform mycelium for further study. Further, microscopic examinations revealed the presence of clamp connections, specialized structures that ensure genetic stability and facilitate cell division during hyphal growth. This method is broadly applicable, though fungi that do not germinate on artificial media may require an alternative approach.Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 383-388